Living standards, poverty and inequality in the UK: 2021 - Jonathan Cribb; Tom Waters; Thomas Wernham; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2021)
This report examines how household incomes were changing in the UK up to the eve of the COVID-19 pandemic, and how other measures of household living standards have changed over the course of the pandemic. In particular, we use the latest official data covering years up to 2019-20 to provide a comprehensive picture of UK household incomes before the pandemic hit. We subsequently use more recent data to examine how the pandemic and associated restrictions on economic activity have radically affected the scope for people to earn an income in the labour market, and what the implications of the pandemic have been for measures of household deprivation. We look at how different groups have fared, with a focus on low-income households, both before and during the pandemic.
Keywords: 330; Armut; Lebensstandard; Einkommensverteilung; Soziale Ungleichheit; Großbritannien